2022
DOI: 10.1149/1945-7111/ac790a
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of a Medium-Mn Third Generation Advanced High Strength Steel during Austenitizing and Intercritical Annealing

Abstract: The effect of the simulated continuous galvanizing line N2-5 vol% H2 process atmosphere oxygen partial pressure (pO2) on the external and internal selective oxidation of a prototype medium-Mn third generation (3G) advanced high strength steel was determined during a two-stage heat treatment cycle (i.e., austenitizing and intercritical annealing) which had previously yielded 3G properties. Thick external oxides (~ 200 nm) were observed after the austenitizing heat treatment, regardless of the process atmosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…However, an additional mechanism for Zn ingress into the substrate is proposed whereby the reactive wetting was facilitated by the selective dissolution of MnO, MnSiO 3 , and Mn 2 SiO 4 during flash pickling. Previous work by the present authors [ 51,52 ] showed that the flash pickling used to restore the substrate surfaces also dissolved some of the internal oxide structures directly connected to the surface. These partially dissolved structures were preserved during the intercritical annealing step and could allow for bath metal infiltration and mechanical interlocking of the coating with the substrate.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…However, an additional mechanism for Zn ingress into the substrate is proposed whereby the reactive wetting was facilitated by the selective dissolution of MnO, MnSiO 3 , and Mn 2 SiO 4 during flash pickling. Previous work by the present authors [ 51,52 ] showed that the flash pickling used to restore the substrate surfaces also dissolved some of the internal oxide structures directly connected to the surface. These partially dissolved structures were preserved during the intercritical annealing step and could allow for bath metal infiltration and mechanical interlocking of the coating with the substrate.…”
Section: Discussionmentioning
confidence: 72%
“…SEM images of the preimmersion surfaces (Figure 2 and 3) show discrete and dispersed nanoscaled oxides that were previously identified as MnCr 2 O 4 [ 51 ] and MnAl 2 O 4 [ 52 ] for steels A and B, respectively. The surfaces were also covered with extruded Fe nodules, which provided additional oxide‐free Fe surfaces to react with the galvanizing bath metal to form the desired Fe 2 Al 5– x Zn x interfacial layer, as shown in Figure 10.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations